Meaning and its Place in the Symbolic Status of the Word - Odilovna, Rakhimova Maftuna (European Journal of Life Safety and Stability (2660-9630), 2021)
This article focuses on the semiotic aspect of linguistics that the description of the sound of the word (nomema) and semema, the related issues, as well as the nature of the word are explained.